(untitled) (Książnica Śląska, 2025)
In the post-plebiscite period in Silesia, the Polish education system began to arise and operate in challenging conditions. Poor housing conditions, lack of educated teaching staff and aggressive activities of German propaganda hindered work in this field. The author of the article recalls the figure of Professor Mieczysława Mitera-Dobrowolska, a teacher at the Women’s Junior High School in Katowice, at Plac Wolności, and an organizer of the Methodological Center for Teachers. The author devotes significant space and attention to the merits of the first Polish teachers working with young people in Silesia, emphasizes the novelty and innovation of the methods and forms of education used at that time and describes the achievements of Polish education.